PENGARUH UU PT TERHADAP KEMITRAAN PERUSAHAAN DENGAN PEMERINTAH - Naek Efendi; Pandri Zulfikar; Tugimin Harjotaruno; Asep Mulyana; Dadang Rachmat; Muhammad Ruhunussa (Berajah Journal, 2026)
Law Number 40 of 2007 concerning Limited Liability Companies (UU PT) which was amended by Law Number 6 of 2023 (UU PT 2023) provides a new legal framework for the operation of limited liability companies in Indonesia. This change has significant implications for partnerships between companies and government, both in the form of public-private partnerships (KPS), public-private partnership (PPP), and other partnership schemes. This study analyzes the influence of UU PT on partnerships between companies and government using a normative juridical approach and document study. The results show that UU PT 2023 provides greater structural flexibility, strengthening of corporate governance, and shareholder protection that impacts partnership dynamics. However, there are challenges related to harmonization with sectoral regulations, uncertainty in implementation, and governance complexity. This study recommends regulatory synchronization, strengthening of monitoring, and development of technical guidelines to optimize partnerships.